Classification of Music Space from the Perspective of Information Philosophy - Shan Zhang (Computer Sciences & Mathematics Forum)
By reviewing the scope of domain division in information philosophy and correlating it with the classification of music spaces, this study highlights the inadequacies of prior research on defining music space types. The previous classification of music space types neglected the significance of spatial information as a crucial dimension in comprehending the characteristics and qualities of music spaces. Information philosophy proposes three characteristics of existence: objective reality, objective non-reality, and subjective non-reality. Music space, as a part of existence, can also be classified according to these characteristics. By reclassifying the types of music space, we can better understand the properties and attributes of each type.